1966
DOI: 10.1007/bf01420690
|View full text |Cite
|
Sign up to set email alerts
|

Social distance and the dying

Abstract: To determine the relative degree of avoidance elicited by the dying, a sample of 203 college students were requested to respond to a social distance scale evaluating 14 ethnic and nonethnic groups. Male subjects indicated basically less avoidance than female subjects, and ethnic groups (e.g. Negro, Mexican-American) were less avoided than the nonethnic groups (e.g. drug addict, dying person, alcoholic). A brief discussion of the problems of mental health workers in their own dealings with the dying is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…A study by Van Orden et al (2006), which also utilized Florida State University undergraduates as participants, found mean scores on an item stating I would not befriend someone who was suicidal tended toward the response option “not at all true” (i.e., mean of approximately 6 on a 1–7 scale ranging from “very true” to “not at all true”). The results of Van Orden et al (2006) demonstrate improvement in social distancing toward suicidal individuals compared to Lester (1993), which in turn demonstrated an improvement compared to Kalish (1966). Additionally, a recent study by Paukert and Pettit (2007) randomly assigned college students to read a vignette describing a depressed individual who either had or had not attempted suicide.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by Van Orden et al (2006), which also utilized Florida State University undergraduates as participants, found mean scores on an item stating I would not befriend someone who was suicidal tended toward the response option “not at all true” (i.e., mean of approximately 6 on a 1–7 scale ranging from “very true” to “not at all true”). The results of Van Orden et al (2006) demonstrate improvement in social distancing toward suicidal individuals compared to Lester (1993), which in turn demonstrated an improvement compared to Kalish (1966). Additionally, a recent study by Paukert and Pettit (2007) randomly assigned college students to read a vignette describing a depressed individual who either had or had not attempted suicide.…”
Section: Discussionmentioning
confidence: 98%
“…Social distance is akin to stigmatization, and refers to the intimacy, indifference, or hostility one displays towards particular people or groups. A study conducted in the 1960s found that people desired more social distance from those who had attempted suicide than from ethnic and religious groups typically discriminated against at the time (Kalish, 1966). A replication of this same study 25 years later found that participants still put considerable distance between themselves and someone who had attempted suicide, though they were willing to put themselves slightly closer than were participants in the earlier study (Lester, 1992–1993).…”
mentioning
confidence: 99%
“…Discrimination may be direct, as shown by studies that demonstrate how people who have attempted suicide are subject to similar processes of “social distancing” as those directed at ethnic or religious minorities (28, 29). Suicides typically leave a total of six or more survivors, with a consequent long-lasting emotional turmoil, which may in some cases end with the survivors’ own suicide (30).…”
Section: Consequences Of Stigma Toward Suicidementioning
confidence: 99%
“…In smaller studies with a tighter focus, other researchers utilized the social distance scale as well. These studies gauged the social distance between doctors and nurses in a mental hospital (Pearlin and Rosenberg ); health professionals and dying patients (Kalish ); immigrants and their rates of naturalization (Walsh ); whites and Asians, blacks, or Hispanics (Wilson ); whites attending interracial churches and African Americans (Yancey ); middle school teachers and the 30 Bogardus groups (Kleg and Yamamoto ); blacks or whites and Jews (Raden ).…”
Section: Introductionmentioning
confidence: 99%